Chemical composition of manganese crusts fom the Southwest Pacific Ocean - H Gary Greene; Neville F Exon (PANGAEA, 2023)
During cruise L582SP of R/V Lee from USGS, dredges performed on the Tonga ridge have retrieved manganese crusts deposited on sandstone formations. These samples have been analysed using atomic absorption spectrophometry techniques.